2015
DOI: 10.1097/mao.0000000000000893
|View full text |Cite
|
Sign up to set email alerts
|

Ossiculoplasty With Titanium Prostheses in Patients With Intact Stapes

Abstract: TORP reconstruction in patients with an intact stapes is associated with good short and longer-term hearing results. Furthermore, hearing outcomes within TORPs remain stable at follow-up >12 months postoperatively. Results did not differ when compared with traditional PORP reconstruction, suggesting that TORP through an intact stapes arch is an acceptable alternative to PORP reconstruction in patients with challenging anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…In our study, data on 27 patients are presented, and a mean improvement in ABG of 10.9 ± 13.5 dB was achieved. Our data are in agreement with another study in which TORP with an intact stapes was investigated; those authors proved that good audiological outcomes could be achieved with this approach . Unfortunately, information about the presence of the malleus handle was lacking in the majority of our cases, indicating the limitations of retrospective data reporting on one hand and the importance of detailed surgical description on the other …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, data on 27 patients are presented, and a mean improvement in ABG of 10.9 ± 13.5 dB was achieved. Our data are in agreement with another study in which TORP with an intact stapes was investigated; those authors proved that good audiological outcomes could be achieved with this approach . Unfortunately, information about the presence of the malleus handle was lacking in the majority of our cases, indicating the limitations of retrospective data reporting on one hand and the importance of detailed surgical description on the other …”
Section: Discussionsupporting
confidence: 90%
“…Our data are in agreement with another study in which TORP with an intact stapes was investigated; those authors proved that good audiological outcomes could be achieved with this approach. 23 Unfortunately, information about the presence of the malleus handle was lacking in the majority of our cases, indicating the limitations of retrospective data reporting on one hand and the importance of detailed surgical description on the other. 24 Interestingly, the creation or obliteration of an open mastoid cavity had no effect on audiological outcome in our cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, a slight movement of a PORP can result in changes in the axis or fulcrum of the ossicular chain and affect the sound transfer process. 24 PORP results showed a better success and hearing outcome than TORP, which could be explained by poor stability and inadequate coupling at the TORP-footplate interface of the prosthesis, but it was statically insignificant, which is agreed with other studies. 16,25 In recent study done by Roux et al on 68 patients that compared the hearing outcome between two groups who underwent titanium ossiculoplasty in CWU cases due to cholesteatoma, the results showed that the control of ossicular prosthesis positioning via the posterior tympanotomy does not improve hearing results after ossicular chain reconstruction in cholesteatoma surgery.…”
Section: Discussionsupporting
confidence: 90%
“…The shaft of the TORP needs to be displaced by only a fraction of a millimeter for it to get disconnected from the footplate and fall down. Alternatively, a slight movement of a PORP can result in changes in the axis or fulcrum of the ossicular chain and affect the sound transfer process …”
Section: Discussionmentioning
confidence: 99%
“…While some literature sees TORP reconstruction in cholesteatoma ears less favorable compared with PORPs or the intact ossicular chain (2,7) other studies have shown different results (8). Furthermore, the analyzed cohort consists of patients with mostly longstanding middle ear ventilation problems, with 75% of them already having had previous ear surgeries for cholesteatoma.…”
Section: Discussionmentioning
confidence: 98%